Dinamika Habitus dan Modal dalam Hara: Analisis Struktur Sosial Pierre Bourdieu terhadap Tiga Cerpen Najib Mahfuz: The Dynamics of Habitus and Capital in Hara: Pierre Bourdieu's Social Structure Analysis of Three Short Stories by Najib Mahfuz - Zaid, Muhammad; Buana, Cahya; Mawardi , Mawardi; Daulay, Heeral Manna; Faiz, Mohammad (Information Technology and Science(ITScience), 2025)
This study aims to analyze the dynamics of complex social structures in Najib Mahfuz's literary works through the lens of Pierre Bourdieu's sociological approach to literature. The background of this study is based on Hara's central position in Mahfuz's narrative, which serves as a microcosm of Egyptian society, marked by value conflicts and power struggles. Using a qualitative descriptive method with a textual approach, this study dissects three selected short stories: